Does the Gap Between East and West Still Exist? a Study of Indonesia’s Disparities - Robinson Sihombing, Pardomuan (Udayana Journal of Social Sciences and Humanities; Vol 3 No 1 (2019): UJoSSH, Feburary 2019DO - 10.24843/UJoSSH.2019.v03.i01.p01, 2019)
Indonesia is a large country with many classical problems. One of the problems still faced by Indonesia is the disparity between Western Indonesia and Eastern Indonesia. Western Indonesia is synonymous with developed and prosperous regions, while East Indonesia is identical to the developing region, the area that left behind. The Indonesian government is implementing various programs to reduce disparities between the two regions. This study aims to map the most striking aspects of the disparity between Western and Eastern Indonesia using discriminant analysis. The variables used are poverty, gini ratio, unemployment, HDI, GEI, GDI, economic growth, sanitation access, and IDI. The results showed that the most distinguishing aspects of the two regions were poverty, unemployment, GDI, and access to sanitation. Thus, it is expected that the policies implemented by the government can prioritize these issues to accelerate equity throughout Indonesia.